The Effects of Capital Adequacy Ratio, Non-Performing Loan, Loan to Deposit Ratio, and Return on Assets on Stock Prices in Banking Sector over the Period 2015 – 2019 - Digdowiseiso, Kumba (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the effects of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Return on Asset (ROA) on the stock prices of banking sector listed on the Indonesia Stock Exchange over the period 2015 – 2019. The sampling technique used was purposive sampling, which generated a sample of 24 companies. This study used secondary data in the form of financial reports which can be obtained from the Indonesia Stock Exchange. The analysis technique used in this research was Fixed Effects regression through the assistance of STATA 16.0 as a statistical software. The results showed that CAR, NPL, LDR and ROA simultaneously had a significant effect on stock prices. However, each partially had a positive and insignificant effect on stock prices.